Managing Careers in Organizations - Ke, Rongzhu; Li, Jin; Powell, Michael (Journal of Labor Economics, 2018)
Firms’ organizational structures impose constraints on their ability to use promotion-based incentives. We develop a framework for identifying these constraints and exploring their consequences. We show that firms manage workers’ careers by choosing personnel policies that resemble an internal labor market. Firms may adopt forced turnover policies to keep lines of advancement open, and they may alter their organizational structures to relax these constraints. This gives rise to a trade-off between incentive provision at the worker level and productive efficiency at the firm level. Our framework generates novel testable implications that connect firm-level characteristics with workers’ careers.